2022
DOI: 10.3390/su14127312
|View full text |Cite
|
Sign up to set email alerts
|

How Energy Price Distortions Affect China’s Economic Growth and Carbon Emissions

Abstract: China’s energy market reform is characterized by “asymmetry” as a result of the transition from a planned economy to a market economy, leading to typical distortions in energy prices. Using panel data from 30 Chinese provinces during 2006–2018, this paper examines the impact of the price distortions of fossil energy sources (coal, oil, and natural gas) as well as renewable energy on China’s economic growth and carbon emissions. The results show that coal price distortion is the highest among the fossil energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Similarly, Li and Leung [50], Mukhtarov et al [51], Karacan et al [52], and Mukhtarov et al [53] confirmed the role of energy prices on renewable energy consumption, and further affects the achievement of sustainable development goals. Umar et al [54] found that effective energy price policies can reduce carbon emissions and achieve SDGs; Ma et al [55], Sha et al [56], Lee and Chong [57], Guo et al [58], Malik et al [59], and Ike et al [60] also confirmed the same point.…”
Section: Cluster Analysis Of Co-cited Articlesmentioning
confidence: 82%
“…Similarly, Li and Leung [50], Mukhtarov et al [51], Karacan et al [52], and Mukhtarov et al [53] confirmed the role of energy prices on renewable energy consumption, and further affects the achievement of sustainable development goals. Umar et al [54] found that effective energy price policies can reduce carbon emissions and achieve SDGs; Ma et al [55], Sha et al [56], Lee and Chong [57], Guo et al [58], Malik et al [59], and Ike et al [60] also confirmed the same point.…”
Section: Cluster Analysis Of Co-cited Articlesmentioning
confidence: 82%
“…Based on the measures of Ju et al (2019) and Sha et al (2022), this paper calculates the degrees of price distortions for the four energy sources, and the data sources are similar to that literature. The degree of fossil energy price distortions is calculated using the deviation between the actual and theoretical energy prices, as follows.…”
Section: Measurement Of Distortions In Energy Pricesmentioning
confidence: 99%
“…The data used to calculate energy price distortions in this paper are from Sha et al (2022), but unlike that, the time span is updated to 2020. There are several reasons for updating the time period: 1) To accurately measure the degrees of distortions and present more current information on energy price distortions in China.…”
Section: Analysis Of Distortions In Energy Pricesmentioning
confidence: 99%
“…Finally, the study of industrial structure transformation and upgrading is necessary to enhance the international competitiveness of industries. The international competitiveness of industry refers to the competitiveness of a particular industry in a country or region, relative to the same industry in other countries or regions, in terms of production efficiency, meeting market demand, and sustained profitability [8][9][10].…”
Section: Introductionmentioning
confidence: 99%